Practice as research : approaches to creative arts enquiry - Barrett, Estelle; Bolt, Barbara (Professor of art) (Bloomsbury Visual Arts, 2019)
Practice-led research is a burgeoning area across the creative arts, with studio informed doctorates frequently favoured over traditional approaches to research. Practice as Research: Approaches to Creative Arts Enquiry is specifically designed as a training tool and is structured on the model used by most research programmes. A comprehensive introduction lays out the book's framework and individual chapters provide concrete examples of studio-based research in art, film and video, creative writing and dance. Comprehensive in its approach, the volume draws on thinkers including Deleuze, Bourdieu and Heidegger in its examination of the relationship between practice and theory demonstrating how practice can operate as a valid alternative mode of enquiry to traditional scholarship -- Publisher's Website.